2011
DOI: 10.1007/s00502-011-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential of plasmonics in photovoltaic solar cells

Abstract: One of the most promising ways to enhance the localized light absorption and to improve the efficiency of extremely thin solar cells is to use plasmonic structures. Plasmons are embedded metal nanostructures which can localize incident light on a sub-micrometric scale enabling light concentration and trapping. The current research shows that the optical broadband absorption in thin-film solar cells can be enhanced due to the local field enhancement by surface plasmons, leading to lower recombination currents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…23 In solar cell fabrication, the efficiency of the cell can be improved by utilizing the plasmonic metallic/ bimetallic NPs which scatter the light efficiently and trap optical energy through SPR. 24,25 Our earlier works on ULAL focused on optimizing the generation of NPs and NSs by changing the surrounding liquid, 5 scanning parameters, 6 input angle of incidence, 7 the shape of input laser pulses, 8 etc. A few of the earlier reports suggested the fabrication of Ag−Au NPs (a) based on post irradiation of colloidal mixtures by laser pulses inducing an alloying process, 16 which was reported to occur through core− shell intermediates 18 (b) entailing ablation of silver targets in the presence of gold nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In solar cell fabrication, the efficiency of the cell can be improved by utilizing the plasmonic metallic/ bimetallic NPs which scatter the light efficiently and trap optical energy through SPR. 24,25 Our earlier works on ULAL focused on optimizing the generation of NPs and NSs by changing the surrounding liquid, 5 scanning parameters, 6 input angle of incidence, 7 the shape of input laser pulses, 8 etc. A few of the earlier reports suggested the fabrication of Ag−Au NPs (a) based on post irradiation of colloidal mixtures by laser pulses inducing an alloying process, 16 which was reported to occur through core− shell intermediates 18 (b) entailing ablation of silver targets in the presence of gold nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, Au–Ag NPs have applications in solar cell fabrication, microelectronics, and sensor fabrication . In solar cell fabrication, the efficiency of the cell can be improved by utilizing the plasmonic metallic/bimetallic NPs which scatter the light efficiently and trap optical energy through SPR. , …”
Section: Introductionmentioning
confidence: 99%
“…The resonance of most metallic nanoparticles is in the visible or infrared regions of the electromagnetic spectrum; however, this also depends on size, shape, and spacing of the metallic particles as well as the dielectric properties of the surrounding medium [ 5 - 7 ]. Most previous studies have shown that silver (Ag) and gold (Au) nanoparticles (NPs) can be used in bulk wafer-based C-Si solar cells or thin-film Si solar cells where the NPs are deposited on one surface of the solar cells [ 1 , 3 , 4 , 8 - 12 ]. However, few studies have examined the effects of metallic NPs deposited on the front and back surfaces of a thin Si solar cell [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltaic solar cells are used to generate electricity by converting the incident light into electric energy [1,2]. This field involves the use of solar cells (SCs) with heavy silicon layer [3], as the optical path in absorber dish was lengthier.…”
Section: Introductionmentioning
confidence: 99%